Effects of occupational exposure to mercury vapor on lymphocyte micronuclei. - Barregard, Lars; Hogstedt, B; Schutz, A; Karlsson, Antti; Sallsten, G; Thiringer, G (Scandinavian Journal of Work, Environment & Health, 1991)
For 26 chloralkali workers exposed to inorganic mercury and 26 age-matched, occupationally unexposed referents, the frequency and size distribution of micronuclei were determined in peripheral lymphocytes stimulated with either phytohemagglutinin or pokeweed mitogen. For the exposed workers the mean concentrations of mercury in urine, plasma, and erythrocytes were 16 nmol/mmol of creatinine, 48 nmol/l, and 78 nmol/l, respectively, and their mean exposure time was 10 years. Neither the frequency nor the size of micronuclei was significantly different in the two groups; nor were there any correlations to current mercury levels. However, in the exposed group, and with phytohemagglutinin as the mitogen, a statistically significant correlation between previous exposure to mercury (cumulative exposure or number of blood mercury peaks) and the frequency of micronuclei was found. This association was also present when the effects of age and smoking were allowed for, and it may indicate an accumulation of cytogenetic effects in T-lymphocytes.